Total and Viable Legionella pneumophila Cells in Hot and Natural Waters as Measured by Immunofluorescence-Based Assays and Solid-Phase Cytometry - Parthuisot, N. (American Society for Microbiology, 2011)
A new method was developed for the rapid and sensitive detection of viable Legionella pneumophila. The method combines specific immunofluorescence (IF) staining using monoclonal antibodies with a bacterial viability marker (ChemChrome V6 cellular esterase activity marker) by means of solid-phase cytometry (SPC). IF methods were applied to the detection and enumeration of both the total and viable L. pneumophila cells in water samples. The sensitivity of the IF methods coupled to SPC was 34 cells liter(−1), and the reproducibility was good, with the coefficient of variation generally falling below 30%. IF methods were applied to the enumeration of total and viable L. pneumophila cells in 46 domestic hot water samples as well as in cooling tower water and natural water samples, such as thermal spring water and freshwater samples. Comparison with standard plate counts showed that (i) the total direct counts were always higher than the plate counts and (ii) the viable counts were higher than or close to the plate counts. With domestic hot waters, when the IF assay was combined with the viability test, SPC detected up to 3.4 × 10(3) viable but nonculturable L. pneumophila cells per liter. These direct IF methods could be a powerful tool for high-frequency monitoring of domestic hot waters or for investigating the occurrence of viable L. pneumophila in both man-made water systems and environmental water samples.